Trypanosoma cruzi infection in the human population of the Bolivian Chaco: four serosurveys over a 26-year period (1987-2013) - Michele Spinicci; Simona Gabrielli; David Rojo; Herlan Gamboa; Fabio Macchioni; Antonia Mantella; Yunni Lara; Ana Liz Villagrán; Mimmo Roselli; Marianne Strohmeyer; Claudia Cinelli; Giampaolo Corti; et al. (Journal of Infection in Developing Countries)
Introduction: Chagas disease (CD) remains a public health concern in several Latin American countries. At global level, Bolivia has the highest CD burden and the Chaco region, in the southeast of the country, is the most affected area. We report the results of four serosurveys for Trypanosoma cruzi antibodies, carried out approximately ten years apart from each other, during the lapse 1987-2013, in different localities of the Bolivian Chaco.